2016
DOI: 10.5194/aab-59-215-2016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carnosic acid, selenized yeast, selenate and fish oil affected the concentration of fatty acids, tocopherols, cholesterol and aldehydes in the brains of lambs

Abstract: Abstract. The function of the brain is to exert centralized control over the other internal organs and tissues of the body. Thus, the objective of our studies was to evaluate changes in the concentration of fatty acids (FAs), cholesterol (CHOL), cholest-4-en-3-one (CHOL-4-3), tocopherols, malondialdehyde (MDA) and fatty aldehydes in the brains of lambs fed supplemented diets. Thirty male Corriedale lambs with a body weight of 30.5 ± 2.6 kg were allotted to five groups of six lambs and housed individually. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…What is more, CA added to diets has the ability to modify the microbial population in the rumen and, hence, the biosynthesis yields of volatile compounds, and UFA isomerisation and biohydrogenation in the rumen (Morán et al 2012a, Miltko et al 2016. Our current study and other studies have shown that CA added to diets with or without Se (as Y Se or VI Se) affected fatty acids profiles, the contents of cholesterol, its oxidation products and the accumulation of carbonyl moieties on proteins produced by oxidative stress in animal tissues (Ibarra et al 2011, Morán et al 2012a, Rozbicka-Wieczorek et al 2016a, 2016c. In accordance with the above, all experimental diets reduced the content of MDA, as well as the values of the PUFA peroxidation index in the PIF and SCF (Krajewska-Bienias et al 2017), compared to the control diet.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…What is more, CA added to diets has the ability to modify the microbial population in the rumen and, hence, the biosynthesis yields of volatile compounds, and UFA isomerisation and biohydrogenation in the rumen (Morán et al 2012a, Miltko et al 2016. Our current study and other studies have shown that CA added to diets with or without Se (as Y Se or VI Se) affected fatty acids profiles, the contents of cholesterol, its oxidation products and the accumulation of carbonyl moieties on proteins produced by oxidative stress in animal tissues (Ibarra et al 2011, Morán et al 2012a, Rozbicka-Wieczorek et al 2016a, 2016c. In accordance with the above, all experimental diets reduced the content of MDA, as well as the values of the PUFA peroxidation index in the PIF and SCF (Krajewska-Bienias et al 2017), compared to the control diet.…”
Section: Discussionsupporting
confidence: 50%
“…Recent studies have indicated that inorganic and organic Se-compounds affect microbial populations and microorganism activity (Ošt'ádalová 2012, Kišidayová et al 2014Kišidayová et al , Čobanová et al 2017, as well as fatty acid (FA) metabolism (like enzymatic isomerisation and biohydrogenation of UFA) in the rumen of ruminants or in in vitro incubated ruminal fluids (Czauderna et al 2012a, Miltko et al 2016, Rozbicka-Wieczorek et al 2016a, 2016b, 2016c, Białek et al 2020. Our previous studies have indicated that dietary carnosic acid (CA), selenized yeast ( Y Se) or VI Se affect the concentrations of FA, total cholesterol (TCh), tocopherols and malondialdehyde (MDA, the marker of PUFA per-oxidation) in the liver, brain, muscles, blood and subcutaneous fat of lambs (Czauderna et al 2009b, 2011, Rozbicka-Wieczorek et al 2016b, 2016c.…”
Section: Manuscript Received August 2020mentioning
confidence: 99%
“…The current study showed that compared to the control diet, the experimental diet enriched only in C-A reduced the concentrations of γ-T, α-TAc and Σall-Ts in the kidneys. At the same time, the CA diet increased oxidative stress in the kidneys, as well as in the brain (Rozbicka-Wieczorek et al, 2016a), liver (Rozbicka-Wieczorek et al, 2016b), muscles (Czauderna et al, 2018), whole blood (Czauderna et al, 2017) and rumen-surrounding fat (Białek and Czauderna, 2019). Considering the above, it is clear that the CA diet, without additional antioxidants (Se-Y or Se-VI) revealed the strongest oxidative activity in the kidneys as compared to the control diet.…”
Section: Tocopherols Oxidative Stress Hypocholesterolemic/hypercholesterolemic Fas Ratio and Thrombogenic And Atherogenic Indices Of The mentioning
confidence: 86%
“…, where: C αT , C αTAc , C γT and C δT -concentrations of α-tocopherol, α-tocopheryl acetate, γ-tocopherol and δ-tocopherol, respectively; 1.49, 1.36, 0.15 and 0.05 are coefficients of biological activity of tocopherols (Zu and Ip, 2003;Rozbicka-Wieczorek et al, 2016a).…”
Section: Analytical Methods and Chromatographic Equipmentmentioning
confidence: 99%
See 1 more Smart Citation